Percutaneous tracheostomy by Griggs technique: a retrospective analysis - Lagoo, Jui Yeshavant; D’Souza, Moses Charles; Appanervanda, Kutappa Muthanna (International Journal of Research in Medical Sciences, 2017)
Background: The scope of percutaneous tracheostomy (PCT) is increasing with experience with successful conduct in conditions traditionally described as contra indications such as difficult anatomy, bleeding diathesis and high ventilatory requirement. The objectives of this study were to assess the safety of PCT in patients with obesity, short neck, thrombocytopenia, coagulopathy, high FiO2 and PEEP requirement. We also aimed to determine complication rate and average time required. Methods: This retrospective study was conducted in the surgical intensive care unit at a tertiary care centre. Seventy five patients who underwent PCT by Griggs technique, with ultrasonographic and bronchoscopic guidance during a period of one year from January to December 2014 were included. Age, sex, height, weight, BMI, platelet count, INR, crico sternal distance and duration of procedure were noted. We analyzed all high risk factors and peri procedural complications. Results: Obesity was present in 5 (6.66%), short neck in 6 (8%), coagulopathy in 25 (33.33%), thrombocytopenia in 22 (29.33%), high FiO2 requirement in 28 (37.33%) and high PEEP requirement in 30 (40%) patients. Minor complications were present in 11 patients (14.66%). No life threatening complications were noted. One patient required conversion into open tracheostomy. The average time taken for PCT was 4.87 ± 1.1 min. Conclusion: PCT can be safely performed in patients with obesity, short neck, thrombocytopenia, coagulopathy and high ventilatory requirement with minimal complication rate, aided by tools like ultrasonography and fiberoptic bronchoscope.